2022
DOI: 10.1111/ppc.13037
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between self‐regulated learning in clinical nursing practice and self‐efficacy: A cross‐sectional study among nursing students

Abstract: Purpose: The aim is to examine self-regulated learning and self-efficacy levels of nursing students, the relationship between them, and to reveal the variables that make a significant difference.Design and Methods: This descriptive, cross-sectional study was conducted with a total of 417 nursing students. The data were collected using the Self-Regulated Learning Scale in Clinical Nursing Practice and Self-Efficacy Scale.Findings: Nursing students have high self-regulated learning (60.28 ± 11.47) and moderate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…5 The studies conducted before the COVID-19 pandemic in the literature were examined, it was found that the self-regulated learning levels of nursing students for clinical practice were good. 4,[6][7][8][9][10][11][12][13]15,26 The fact that this research was carried out during the COVID-19 pandemic may be the cause of the discrepancy between the results in the literature and the current study results. Several substitute clinical training techniques, including real-time online simulations using Zoom or YouTube (PayPal employee, California, ABD) streaming, have been adopted by academic institutions communities, and hospitals because nursing requires clinical training, which has been significantly hampered by the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…5 The studies conducted before the COVID-19 pandemic in the literature were examined, it was found that the self-regulated learning levels of nursing students for clinical practice were good. 4,[6][7][8][9][10][11][12][13]15,26 The fact that this research was carried out during the COVID-19 pandemic may be the cause of the discrepancy between the results in the literature and the current study results. Several substitute clinical training techniques, including real-time online simulations using Zoom or YouTube (PayPal employee, California, ABD) streaming, have been adopted by academic institutions communities, and hospitals because nursing requires clinical training, which has been significantly hampered by the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 67%
“…4 Zimmerman's theoretical framework describes self-regulated learning as a mental process in which nursing students have control over their learning processes, which aids in behaviour management and facilitates the cognitive, emotional, and motivational aspects of learning. [5][6][7][8] This model consists of 3 stages: foresight, performance, and self-reflection. Self-regulated learners effectively set goals during the foresight phase.…”
mentioning
confidence: 99%
“…(9) This model gives a useful structure for learning about and improving EI in nursing. In nursing, Self-awareness helps nurses identify their sentiments and prejudices and manage their emotions to give better care (10) and self-regulation is essential in high-stress conditions as it enables nurses to maintain their composure and calmness in the face of challenging circumstances. (11) Nurses who possess high levels of motivation are more persuaded to employ additional effort to safeguard the overall welfare of their patients.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…2024 January; 3 (1) resolving patient concerns. (10) The possession of a high EI by nurses facilitates their ability to effectively convey intricate medical information to patients and their families in an easily understandable manner.…”
Section: Reviewmentioning
confidence: 99%